SENTENCE PATTERNS IN DESCRIPTIVE TEXT OF SENIOR HIGH SCHOOL ENGLISH TEXTBOOK - Selviana Napitupulu; Leonita Manihuruk (Visi Sosial Humaniora, 2020)
This research is aimed at the Sentence Patterns in Descriptive Text of Senior High School English Textbook. Focusing on the problem statements, there are two cases in this research. They are “What types of sentence patterns are found in Descriptive Text of Senior High School English Textbook and what are the found of each elements of the sentence patterns in Descriptive Text of Senior High School English Textbook. This research, applied descriptive qualitative method. The data is collected by documenting. The data is taken from Descriptive Text of Senior High School English Textbook. The procedure of analyzing the data start by analyzing about sentence patterns types based on Brown’s theory. Then find the dominant of the sentence patterns types of Descriptive text of Senior High School English Textbook and the elements of Sentence Pattern in English textbook. Based on the results, the researchers found out 5 patterns which were used in the descriptive text of senior high school English textbook. The sentence pattern which is was frequently used was pattern: S + V + SC and the elements used in the sentence pattern was Phrase namely, Noun Phrase. Finally, the researchers hope that the results can help English learners to improve their understanding on sentence patterns and the elements of the sentence patterns.